Carbon ceramic resistor containing continuous conductive interlayer and preparation method and application thereof
By adopting a multi-stage pore structure continuous ceramic support and a sandwich structure of continuous carbon conductive layer in carbon ceramic resistors, the problem of uneven distribution of carbon materials is solved, the mechanical properties and compressive strength of carbon ceramic resistors are improved, and the mechanical properties and compressive strength of carbon ceramic resistors are extended. Service life.
Patent Information
- Application Number
- CN202411608962.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-27
AI Technical Summary
The uneven distribution of existing carbon ceramic resistors in ceramic materials leads to current breakdown problems, and it is difficult to build a three-dimensional conductive network structure, affecting its mechanical and electrical properties.
The continuous ceramic support and continuous carbon conductive layer are sandwiched structures using a multi-stage pore structure. By depositing a continuous carbon conductive layer in the multi-stage pore structure of the ceramic support and filling the continuous ceramic filling layer therebetween, ceramic-carbon material is formed. -The new structure of ceramics ensures uniform dispersion and continuous through carbon materials.
The uniform dispersion of carbon materials in the ceramic matrix is achieved, the mechanical properties and compressive strength of carbon ceramic resistance are improved, the service life is extended, and the bulk density is increased to ≥2.20g/cm3 and the compressive strength is increased to ≥130MPa.
Smart Images

Figure CN119207928A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special material production for electrical equipment, and in particular relates to a carbon ceramic resistor containing a continuous conductive interlayer and a preparation method and application thereof. Background Art
[0002] Ceramic resistors play a key role in UHV and UHV AC systems. They can effectively limit overvoltage when the switch is closed. They are mainly used in circuit breakers in UHV transmission systems to protect the safety of power transmission and transformation equipment and prevent the high voltage and high current that appear at the moment of closing from damaging the system. They are one of the most important protective components of UHV transmission systems. This type of resistor has excellent high-voltage current impulse tolerance, a wide resistivity range, is essentially a non-inductive resistor, can effectively absorb high pulse energy, and is suitable for a variety of environments. Therefore, it is crucial to the safe operation of the power grid.
[0003] Carbon ceramic resistors are a new type of resistor material developed based on traditional ceramic resistors to cope with more demanding application environments and technical challenges. It not only inherits the advantages of the original products, but also has the ability to withstand extreme working conditions (such as extremely high temperatures and strong vibrations). However, at present, a few domestic units have carried out relevant basic research on carbon ceramic switching resistors, but have not yet mastered the core technology of carbon ceramic resistor production, and no market-oriented products have appeared. It is urgent to carry out applied technology research with product development as the goal.
[0004] The technical difficulties of high-performance switching carbon ceramic resistors and their preparation are how to construct a three-dimensional conductive network structure in ceramic materials, regulate the resistivity range of ceramic switching resistors to their target requirements, and avoid problems such as the addition of too little carbon material failing to meet the resistivity requirements and too much addition affecting their sintering behavior, thereby reducing their mechanical properties. Especially in ceramic materials, the agglomeration and segregation of carbon materials may significantly affect their performance. Under experimental or actual working conditions, this uneven distribution causes certain areas of the resistor to absorb energy and release heat. As a result, these concentrated energy-absorbing areas may be overloaded due to the strong action of the current, ultimately leading to current breakdown of the resistor. Therefore, during the design and manufacturing process, special attention should be paid to the uniform distribution of carbon materials to avoid the problem of resistor breakdown caused by agglomeration and segregation.
[0005] From the above, it can be seen that there is still a need to optimize and develop the preparation technology of carbon ceramic resistors so that the carbon material can achieve a better dispersion effect, and finally fill the three-dimensional carbon-containing conductive network structure in the ceramic matrix, thereby obtaining a carbon ceramic closing resistor with further improved mechanical and electrical properties. Summary of the invention
[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a carbon ceramic resistor containing a continuous conductive interlayer, and a preparation method and use thereof. The carbon ceramic resistor containing a continuous conductive interlayer includes a continuous ceramic support body with a multi-level pore structure, the multi-level pore structure is filled with a continuous ceramic filling layer and a continuous carbon conductive layer, and the continuous carbon conductive layer is located between the continuous ceramic support body and the continuous ceramic filling layer to form an interlayer, which ensures that the conductive carbon material can be evenly dispersed in the ceramic support body, solves the problem of uneven dispersion distribution of the carbon material, and allows the continuous carbon conductive layer to continuously penetrate the ceramic support body to form a three-dimensional conductive network structure.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a carbon ceramic resistor containing a continuous conductive interlayer, comprising:
[0009] A continuous ceramic support having a multi-level pore structure;
[0010] A continuous ceramic filling layer filled in the multi-level pore structure;
[0011] The continuous carbon conductive layer is filled in the multi-level pore structure and is located between the continuous ceramic support and the continuous ceramic filling layer to form an interlayer.
[0012] The dispersion problem of conductive carbon materials is a fundamental problem that affects carbon ceramic resistors. Uneven distribution of conductive carbon materials will cause certain areas of the resistor to absorb energy and release heat, which will eventually lead to current breakdown of the resistor. In the carbon ceramic resistor of the present invention, the conductive carbon material is filled in the multi-level pore structure of the continuous ceramic support, which is equivalent to depositing a continuous carbon conductive layer on the inner pore wall of the continuous ceramic support, and then filling a continuous ceramic filling layer so that the carbon material forms a continuous interlayer between the ceramic materials. This new structure of ceramic-carbon material-ceramic material ensures that the conductive carbon material continuously extends and penetrates the pores of the ceramic support, and can ensure that it is evenly dispersed in the overall ceramic matrix formed by the ceramic support and the ceramic filling layer, effectively solving the problem of uneven dispersion distribution of the carbon material. The volume density of the carbon ceramic resistor product containing a continuous conductive interlayer obtained by the present invention is ≥2.20g / cm 3 The volume density is high, and the carbon ceramic resistor containing continuous conductive interlayer has better mechanical properties, and the compressive strength is ≥130MPa, which prolongs the service life.
[0013] It should be noted that the “continuous” in the continuous ceramic support, the continuous ceramic filling layer and the continuous carbon conductive layer of the present invention refers to the continuity of the structure and organization of the material components themselves.
[0014] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] As a preferred technical solution of the present invention, the continuous ceramic support includes nanopores, micropores and interface pores with successively increasing pore sizes, forming the multi-level pore structure.
[0016] Preferably, the pore size of the nanopore is For example or etc.; the pore size of the micron pore is 100-120μm, for example, 100μm, 102μm, 105μm, 108μm, 110μm, 112μm, 115μm, 118μm or 120μm, etc.; the pore size of the interface pore is 500-800μm, for example, 500μm, 530μm, 550μm, 580μm, 600μm, 630μm, 650μm, 680μm, 700μm, 720μm, 750μm, 780μm or 800μm, etc.
[0017] Preferably, the continuous ceramic support and the continuous ceramic filling layer comprise mullite.
[0018] Preferably, the porosity of the continuous ceramic support is 55% to 65%, for example, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64% or 65%, etc.
[0019] Preferably, the continuous carbon conductive layer comprises a conductive carbon material, and the conductive carbon material comprises spherical graphite.
[0020] Preferably, the thickness of the continuous carbon conductive layer is 20-50 μm, for example, 20 μm, 23 μm, 25 μm, 28 μm, 30 μm, 33 μm, 35 μm, 38 μm, 40 μm, 42 μm, 45 μm, 48 μm or 50 μm.
[0021] Preferably, the volume density of the carbon ceramic resistor containing the continuous conductive interlayer is ≥2.20 g / cm 3 , for example 2.2 g / cm 3 , 2.23g / cm 3 , 2.25g / cm 3 , 2.28g / cm 3 , 2.3g / cm 3 , 2.32g / cm 3 , 2.35g / cm 3 , 2.38g / cm 3or 2.4g / cm 3 etc., apparent porosity ≤ 25%, for example 25%, 23%, 20%, 18%, 15%, 13%, 10%, 8%, 6%, 4%, 2% or 1%, etc.; compressive strength ≥ 130MPa, for example 130MPa, 135MPa, 140MPa, 145MPa, 150MPa, 155MPa, 160MPa, 165MPa, 170MPa, 175MPa or 180MPa, etc.
[0022] In a second aspect, the present invention provides a method for preparing the carbon ceramic resistor containing a continuous conductive interlayer according to the first aspect, comprising:
[0023] Providing a continuous ceramic support body raw material, performing foaming and granulation to obtain a hollow spherical powder, performing compression molding to obtain a first green body, and performing a first sintering to obtain a continuous ceramic support body with a multi-level pore structure;
[0024] Providing a continuous carbon conductive layer raw material, subjecting the obtained continuous ceramic support to a first impregnation in the continuous carbon conductive layer raw material to obtain a second green body, and then subjecting the green body to a second sintering to form a continuous carbon conductive layer to obtain an intermediate;
[0025] A continuous ceramic filling layer raw material is provided, and the obtained intermediate is subjected to a second impregnation in the continuous ceramic filling layer raw material to obtain a third green body, which is then subjected to a third sintering to form a continuous ceramic filling layer, thereby obtaining the carbon ceramic resistor containing a continuous conductive interlayer.
[0026] The preparation method described in the present invention is implemented by first preparing a continuous ceramic support layer with through holes and a multi-level pore structure, then filling and depositing a continuous carbon conductive layer in the internal pores of the continuous ceramic support layer to cover the inner walls of the pores, and finally using ceramic slurry to fill the remaining parts of the pores to form a continuous ceramic filling layer, thereby finally forming a carbon ceramic resistor with a continuous through-type structure.
[0027] As a preferred technical solution of the present invention, based on the total mass parts of the continuous ceramic support raw material and the continuous ceramic filling layer raw material being 100 parts, the continuous ceramic support raw material includes 35 to 45 parts of zeolite, for example, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts or 45 parts; 5 to 15 parts of glass powder, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, etc.
[0028] Preferably, the preparation method also includes providing a continuous ceramic support raw material, mixing it with a first additive to obtain a first mixed raw material, and then subjecting the first mixed raw material to the foaming and granulation; relative to the total mass parts of the continuous ceramic support raw material and the continuous ceramic filling layer raw material being 100 parts, the first additive includes 0.5 to 2 parts of a first dispersant, for example, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts or 2 parts, etc.; and 0.5 to 2 parts of a foaming agent, for example, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts or 2 parts, etc.
[0029] It should be noted that the continuous ceramic support obtained by sintering the preferred continuous ceramic support raw material of the present invention contains mullite material, that is, mullite ceramics with a multi-level pore structure.
[0030] Preferably, the zeolite comprises clinoptilolite, and the zeolite has a pore size of Nanopores, such as or wait.
[0031] The present invention preferably uses zeolite minerals with nanopores to replace the conventionally used corundum and quartz powder, and then cooperates with the foaming, molding and sintering processes. On the basis of the reaction to form mullite ceramics, the continuous ceramic support body can form micron pores and interface pores, and then form a multi-level pore structure of nano-micron-submicron size, which is beneficial to the preparation of a continuous carbon conductive layer and provides a filling deposition template for the uniform dispersion of conductive carbon materials.
[0032] Preferably, the first dispersant includes at least one of polyacrylamide, sodium humate or polymethylsiloxane.
[0033] Preferably, the foaming agent includes at least one of propyl gallate, polyether-modified silicone or polyurethane foam.
[0034] Preferably, except for the foaming agent, the other raw materials of the continuous ceramic support are pre-milled by a first wet ball mill, and then the foaming agent is added to perform the foaming granulation to obtain hollow slurry droplets, which are then dried to obtain the hollow spherical powder.
[0035] The spherical granule powder obtained by the foaming method granulation and drying has certain strength and good fluidity. The certain strength means that the granules can exist stably after granulation and will break when a small pressure is applied later.
[0036] Preferably, the mass ratio of balls to materials in the first wet ball milling is (1-3):1, for example 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1 or 3:1, etc., the rotation speed is 400-500rpm, for example 400rpm, 410rpm, 420rpm, 430rpm, 440rpm, 450rpm, 460rpm, 470rpm, 480rpm, 490rpm or 500rpm, etc., and the time is 1.5-3h, for example 1.5h, 1.8h, 2h, 2.3h, 2.5h, 2.8h or 3h, etc.
[0037] Preferably, the drying temperature is 180-220°C, for example 180°C, 190°C, 200°C, 210°C or 220°C, and the drying time is 1-3h, for example 1h, 1.3h, 1.5h, 1.8h, 2h, 2.3h, 2.5h, 2.8h or 3h.
[0038] Preferably, the press-forming method comprises cold isostatic pressing.
[0039] Preferably, the pressure of the press molding is 10-20 MPa, for example, 10 MPa, 11 MPa, 12 MPa, 13 MPa, 14 MPa, 15 MPa, 16 MPa, 17 MPa, 18 MPa, 19 MPa or 20 MPa.
[0040] Preferably, the temperature of the first sintering is 1400-1600°C, for example, 1400°C, 1430°C, 1450°C, 1480°C, 1500°C, 1520°C, 1550°C, 1580°C or 1600°C; the time is 3-6h, for example, 3h, 3.4h, 3.8h, 4h, 4.2h, 4.6h, 5h, 5.3h, 5.5h, 5.8h or 6h.
[0041] As a preferred technical solution of the present invention, based on the total mass parts of the continuous ceramic support raw material, the continuous carbon conductive layer raw material and the continuous ceramic filling layer raw material being 100 parts, the continuous carbon conductive layer raw material includes 0.5 to 4.5 parts of conductive carbon material, for example, 0.5 parts, 0.8 parts, 1 parts, 1.3 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.3 parts, 3.5 parts, 3.8 parts or 4 parts, etc.
[0042] Preferably, the preparation method further comprises providing a continuous carbon conductive layer raw material, mixing it with a second additive to obtain a second mixed raw material, and then subjecting the obtained continuous ceramic support to the first impregnation in the second mixed raw material; relative to the total mass parts of the continuous ceramic support raw material and the continuous ceramic filling layer raw material being 100 parts, the second additive comprises 0.5 to 1.5 parts of a second dispersant, such as 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts or 1.5 parts, etc.; 1 to 1. 5 parts of polyvinyl alcohol, for example 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts or 1.5 parts, etc.; 0.10-0.20 parts of the first surfactant, for example 0.1 parts, 0.11 parts, 0.12 parts, 0.13 parts, 0.14 parts, 0.15 parts, 0.16 parts, 0.17 parts, 0.18 parts, 0.19 parts or 0.2 parts, etc.; 0.5-1 parts of the first defoaming agent, for example 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts, etc.
[0043] Preferably, the conductive carbon material includes at least one of spherical graphite, expanded graphite or carbon hollow spheres.
[0044] Preferably, the second dispersant comprises polyvinyl pyrrolidone.
[0045] Preferably, the first surfactant comprises a silane coupling agent.
[0046] Preferably, the first defoaming agent comprises polydimethylsiloxane.
[0047] Preferably, the first impregnation method comprises vacuum-assisted centrifugal impregnation.
[0048] Preferably, the second sintering is carried out in a reducing atmosphere, and the temperature of the second sintering is 900-1200°C, for example, 900°C, 950°C, 980°C, 1000°C, 1030°C, 1050°C, 1080°C, 1100°C, 1130°C, 1150°C, 1180°C or 1200°C, etc.
[0049] As a preferred technical solution of the present invention, based on the total mass parts of the continuous ceramic support raw material and the continuous ceramic filling layer raw material being 100 parts, the continuous ceramic filling layer raw material includes 23 to 27 parts of bauxite, such as 23 parts, 23.5 parts, 24 parts, 24.5 parts, 25 parts, 25.5 parts, 26 parts, 26.5 parts or 27 parts, etc.; 14 to 16 parts of kaolin, such as 14 parts, 14.3 parts , 14.5, 14.8, 15, 15.2, 15.5, 15.8 or 16 parts, etc.; 9 to 11 parts of calcium feldspar, such as 9, 9.2, 9.5, 9.8, 10, 10.2, 10.5, 10.8 or 11 parts, etc.; 0.3, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.2 or 2.5 parts, etc.;
[0050] Preferably, the preparation method comprises providing a continuous ceramic filling layer raw material, mixing it with a third additive to obtain a third mixed raw material, and then subjecting the obtained intermediate to the second impregnation in the third mixed raw material; relative to the total mass parts of the continuous ceramic support body raw material and the continuous ceramic filling layer raw material being 100 parts, the third additive comprises 0.5 to 1.5 parts of a third dispersant, for example, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts or 1.5 parts, etc.; 1 to 1.5 parts of Polyvinyl alcohol, for example 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts or 1.5 parts, etc.; 0.10-0.20 parts of the second surfactant, for example 0.1 parts, 0.11 parts, 0.12 parts, 0.13 parts, 0.14 parts, 0.15 parts, 0.16 parts, 0.17 parts, 0.18 parts, 0.19 parts or 0.2 parts, etc.; 0.5-1 parts of the second defoaming agent composition, for example 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts, etc.
[0051] It should be noted that the continuous ceramic filling layer obtained by sintering the preferred continuous ceramic filling layer raw material of the present invention contains mullite material, that is, forms mullite ceramics.
[0052] Preferably, the third dispersant comprises polyvinyl pyrrolidone.
[0053] Preferably, the second surfactant comprises a silane coupling agent.
[0054] Preferably, the second defoaming agent comprises polydimethylsiloxane.
[0055] Preferably, the raw material of the continuous ceramic filling layer is pre-milled by a second wet ball mill.
[0056] Preferably, the ball-to-material mass ratio of the second wet ball milling is (1-3):1, for example 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1 or 3:1, etc., the rotation speed is 300-360rpm, for example 300rpm, 310rpm, 320rpm, 330rpm, 340rpm, 350rpm or 360rpm, etc., and the time is 1.5-3h, for example 1.5h, 1.8h, 2h, 2.3h, 2.5h, 2.8h or 3h, etc.
[0057] Preferably, the second impregnation method comprises vacuum-assisted centrifugal impregnation.
[0058] Preferably, the temperature of the third sintering is 1200-1400°C, for example, 1200°C, 1250°C, 1280°C, 1300°C, 1320°C, 1350°C, 1380°C or 1400°C.
[0059] The present invention adopts a staged multi-step sintering method. By controlling the temperature in stages, the microstructure of the material during the sintering process, such as grain size and distribution, can be more accurately controlled, thereby improving the performance and consistency of the final product. The staged sintering process can reduce common defects in the sintering process, such as porosity, cracks and unevenness, thereby improving the overall quality of the material. The staged process can sinter the material more evenly, making the performance of each part of the final product more consistent, effectively improving the product qualification rate.
[0060] As a preferred technical solution of the present invention, the vacuum-assisted centrifugal dipping method is carried out in a manipulator single-cylinder dipping and spinning integrated coating machine, and the vacuum degree is 0.01 to 0.5 atm, for example, 0.01 atm, 0.03 atm, 0.05 atm, 0.08 atm, 0.1 atm, 0.13 atm, 0.15 atm, 0.18 atm, 0.2 atm, 0.23 atm, 0.25 atm, 0.28 atm, 0.3 atm, 0.33 atm, 0. the rotation speed is 200-400rpm, for example, 200rpm, 230rpm, 250rpm, 280rpm, 300rpm, 330rpm, 350rpm, 380rpm or 400rpm, and the time is 2-5h, for example, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, etc.
[0061] In the present invention, a vacuum-assisted centrifugal impregnation method is used as the impregnation process. Compared with a single impregnation process, vacuum assistance can reduce bubbles and voids, allowing the impregnation slurry to penetrate into the material more evenly, thereby improving the efficiency of impregnation. In a vacuum environment, the liquid penetration rate is usually faster, thereby reducing the time of the entire impregnation process. The vacuum can effectively remove bubbles in the material and reduce defects that may occur during the impregnation process, such as pores, interlayers, and other problems. Centrifugation can evenly distribute the impregnation slurry, and can adjust the concentration and distribution of the impregnation slurry by controlling the centrifugal force, which helps to more accurately control the process parameters, especially the filling amount and thickness of the continuous carbon conductive layer.
[0062] As a preferred technical solution of the present invention, it includes:
[0063] (1) Preparation of a continuous ceramic support:
[0064] A continuous ceramic support material is provided by weight, including 35-45 parts of clinoptilolite, 5-15 parts of glass powder and 0.5-2 parts of a first dispersant, and after mixing, a first wet ball milling is performed, and the ball-material mass ratio is controlled to be (1-3):1, the rotation speed is 400-500 rpm, and the time is 1.5-3 hours to prepare a first mixed slurry; the first dispersant includes at least one of polyacrylamide, sodium humate or polymethylsiloxane; the clinoptilolite has a pore size of Nanopores; adding 0.5 to 2 parts of a foaming agent to the first mixed slurry, wherein the foaming agent includes at least one of propyl gallate, polyether-modified silicone or polyurethane foam; performing foaming and granulation to obtain hollow slurry droplets, and then drying at 180 to 220° C. for 1 to 3 hours to obtain hollow spherical powder; performing cold isostatic pressing of the obtained hollow spherical powder in a mold at 10 to 20 MPa to obtain a first green body, and then performing a first sintering at 1400 to 1600° C. for 3 to 6 hours to obtain a continuous ceramic support having a multi-level pore structure;
[0065] (2) Preparation of continuous carbon conductive layer:
[0066] Providing a continuous carbon conductive layer raw material by mass, including 0.5-4.5 parts of conductive carbon material spherical graphite, 0.5-1.5 parts of second dispersant polyvinyl pyrrolidone, 1-1.5 parts of polyvinyl alcohol, 0.10-0.20 parts of first surfactant silane coupling agent and 0.5-1 parts of first defoaming agent polydimethylsiloxane, wherein the conductive carbon material includes at least one of spherical graphite, expanded graphite or carbon hollow spheres, and mixing them to form a second mixed slurry, and using a vacuum-assisted centrifugal impregnation method, the obtained continuous ceramic support body is first impregnated in the second mixed slurry in a manipulator single-cylinder dip-spin integrated coating machine, and the vacuum degree is controlled to be 0.01-0.5atm, the rotation speed is 200-400rpm, and the time is 2-5h to obtain a second green body, and then a second sintering is performed at 900-1200°C in a reducing atmosphere to form a continuous carbon conductive layer to obtain an intermediate;
[0067] (3) Preparation of continuous ceramic filling layer:
[0068] Provide a continuous ceramic filling layer raw material by weight, including 23-27 parts of bauxite, 14-16 parts of kaolin, 9-11 parts of calcium feldspar, 0.5-1.5 parts of a third dispersant polyvinyl pyrrolidone, 1-1.5 parts of polyvinyl alcohol, 0.10-0.20 parts of a second surfactant silane coupling agent and 0.5-1 parts of a second defoaming agent polydimethylsiloxane, and perform a second wet ball milling after mixing, control the ball-to-material mass ratio to (1-3):1, and the rotation speed to 200-400 rpm, for 1.5 to 3 hours, to prepare a third mixed slurry; using a vacuum-assisted centrifugal impregnation method, the intermediate is secondly impregnated in the third mixed slurry in a manipulator single-cylinder dip-spinning coating machine, the vacuum degree is controlled to be 0.01 to 0.5 atm, the rotation speed is 200 to 400 rpm, and the time is 2 to 5 hours to obtain a third green body, and then a third sintering is performed at 1200 to 1400 ° C to form a continuous ceramic filling layer, thereby obtaining the carbon ceramic resistor containing a continuous conductive interlayer;
[0069] In steps (1) to (3), the total weight of the clinoptilolite, the glass powder, the bauxite, the kaolin and the anorthite is controlled to be 100 parts.
[0070] In a third aspect, a closing resistor comprises the carbon ceramic resistor containing a continuous conductive interlayer as described in the first aspect.
[0071] In a fourth aspect, a method for manufacturing the closing resistor described in the third aspect is provided, wherein the carbon ceramic resistor containing the continuous conductive interlayer is subjected to mechanical grinding treatment and electrode coating in sequence to obtain the closing resistor.
[0072] It should be noted that due to space limitations and to avoid redundancy, the present invention does not exhaustively list all point values within the above numerical range, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0073] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0074] The present invention allows the conductive carbon material to be filled and precipitated in the multi-level pore structure of the continuous ceramic support to form a continuous carbon conductive layer, and then fills and sets a continuous ceramic filling layer to construct a new carbon ceramic resistor structure of ceramic-carbon material-ceramic material, thereby ensuring that the conductive carbon material continuously extends and penetrates in the pores of the ceramic support, and can ensure that it is evenly dispersed in the overall ceramic matrix formed by the ceramic support and the ceramic filling layer, effectively solving the problem of uneven dispersion distribution of the carbon material. The volume density of the carbon ceramic resistor product containing a continuous conductive interlayer obtained by the present invention is ≥2.20g / cm 3 The volume density is high, and the carbon ceramic resistor containing continuous conductive interlayer has better mechanical properties, and the compressive strength is ≥130MPa, which prolongs the service life.
[0075] The preparation method of the present invention preferably uses zeolite minerals to replace conventional raw materials corundum and quartz powder, and combines with a foaming method to form a continuous ceramic support body with a multi-level continuous through-pore structure; through a vacuum-assisted impregnation process, the conductive carbon material can form a continuous, thickness-controlled conductive interlayer in the multi-level pores; a multi-step sintering method is used to improve the bonding strength of each structural layer and improve its mechanical strength, thereby increasing the service life of the carbon ceramic resistor and, at the same time, greatly improving the product qualification rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 is a schematic diagram of a cross section of a carbon ceramic resistor with a continuous conductive interlayer in Example 1;
[0077] In the figure: 1-continuous ceramic support, 2-continuous ceramic filling layer, 3-continuous carbon conductive layer. DETAILED DESCRIPTION
[0078] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0079] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0080] Example 1
[0081] This embodiment provides a carbon ceramic resistor containing a continuous conductive interlayer, such as Figure 1 As shown, including:
[0082] The continuous ceramic support 1 includes mullite, and the continuous ceramic support 1 has a multi-level pore structure, including a pore size of Nanopores, micropores of 100-120 μm and interfacial pores of 500-800 μm, with a porosity of 58%;
[0083] A continuous ceramic filling layer 2, comprising mullite, wherein the continuous ceramic filling layer 2 is filled in the multi-level pore structure;
[0084] The continuous carbon conductive layer 3 includes spherical graphite. The continuous carbon conductive layer 3 is filled in the multi-level pore structure and is located between the continuous ceramic support 1 and the continuous ceramic filling layer 2 to form an interlayer.
[0085] The method for preparing the carbon ceramic resistor containing a continuous conductive interlayer comprises:
[0086] (1) Preparation of a continuous ceramic support:
[0087] A continuous ceramic support material is provided in parts by mass, including 40 parts of clinoptilolite, 10 parts of glass powder and 1 part of a first dispersant ammonium polyacrylate, wherein the clinoptilolite has a pore size of After mixing, the first wet ball milling is carried out in an omni-directional planetary ball mill, and the ball-to-material mass ratio is controlled to be 2:1, the rotation speed is 500rpm, and the time is 2h to prepare a first mixed slurry; then 1 part of a foaming agent propyl gallate is added to the mixed slurry for foaming and granulation to obtain hollow slurry droplets, and then a blower dryer is used to dry at 200°C for 2h to obtain a hollow spherical powder; the obtained hollow spherical powder is cold isostatically pressed in a specific mold at 15MPa to obtain a first green body, and then a first sintering is carried out at 1500°C for 1h to obtain a continuous ceramic support with a multi-level pore structure;
[0088] (2) Preparation of continuous carbon conductive layer:
[0089] Providing a continuous carbon conductive layer raw material by mass, including 3 parts of conductive carbon material spherical graphite, 1 part of a second dispersant polyvinyl pyrrolidone, 1.5 parts of polyvinyl alcohol, 0.20 parts of a first surfactant silane coupling agent, and 1 part of a first defoaming agent polydimethylsiloxane, mixing them to form a second mixed slurry, using a vacuum-assisted centrifugal impregnation method, and performing a first impregnation of the obtained continuous ceramic support in the second mixed slurry in a manipulator single-cylinder dip-spinning coating machine, controlling the vacuum degree to 0.1 atm, the rotation speed to 300 rpm, and the time to 3 hours to obtain a second green body, and then performing a second sintering at 900° C. for 1 hour in a reducing atmosphere to form a continuous carbon conductive layer, and obtaining an intermediate;
[0090] (3) Preparation of continuous ceramic filling layer:
[0091] A continuous ceramic filling layer raw material is provided by weight, including 25 parts of bauxite, 15 parts of kaolin, 10 parts of calcium feldspar, 1 part of a third dispersant polyvinyl pyrrolidone, 1.5 parts of polyvinyl alcohol, 0.2 parts of a second surfactant silane coupling agent and 1 part of a second defoaming agent polydimethylsiloxane, and after mixing, a second wet ball milling is performed, and the ball-to-material mass ratio is controlled to be 2:1, the rotation speed is 300 rpm, and the time is 1.5 to 3 hours to prepare a third mixed slurry; a vacuum-assisted centrifugal impregnation method is adopted, and the obtained intermediate is secondly impregnated in the third mixed slurry in a manipulator single-cylinder dip-spinning coating machine, and the vacuum degree is controlled to be 0.1 atm, the rotation speed is 300 rpm, and the time is 3 hours to obtain a third green body, and then a third sintering is performed at 1300°C to form a continuous ceramic filling layer, and the carbon ceramic resistor containing a continuous conductive interlayer is obtained.
[0092] Example 2 and Example 3
[0093] Embodiments 2 and 3 respectively provide a carbon ceramic resistor containing a continuous conductive interlayer, including:
[0094] The continuous ceramic support includes mullite, and the continuous ceramic support has a multi-level pore structure, including a pore size of Nanopores, micropores of 100-120 μm and interfacial pores of 500-800 μm, with a porosity of 58%;
[0095] A continuous ceramic filling layer, comprising mullite, wherein the continuous ceramic filling layer is filled in the multi-level pore structure;
[0096] The continuous carbon conductive layer comprises spherical graphite, is filled in the multi-level pore structure, and is located between the continuous ceramic support and the continuous ceramic filling layer to form an interlayer.
[0097] The preparation methods of the carbon ceramic resistors containing continuous conductive interlayers described in Examples 2 to 3 respectively change at least one of the continuous ceramic support raw materials, the continuous carbon conductive layer raw materials or the continuous ceramic filling layer raw materials, as shown in Table 1. Except for the above, other conditions are exactly the same as those in Example 1.
[0098] Table 1
[0099]
[0100] Comparative Example 1
[0101] Compared with Example 1, in Comparative Example 1, a vacuum impregnation method is adopted without centrifugal assistance, and the obtained intermediate is subjected to a second impregnation in the third mixed slurry, the vacuum degree is controlled to be 0.1atm, the rotation speed is 300rpm, and the time is 3h to obtain a third green body, and then a third sintering is carried out at 1300°C to form a carbon ceramic resistor.
[0102] Comparative Example 2
[0103] This comparative example provides a carbon ceramic resistor, and the preparation method thereof comprises:
[0104] The raw materials, by mass fraction, include 55% bauxite, 35% kaolin, 8% potassium feldspar, 2% MgB2, and are doped with 4.5% nano-scale superconducting carbon black, 1% polyvinyl pyrrolidone, 1.5% polyvinyl alcohol, and 0.20% silane coupling agent. The above raw materials are uniformly mixed and ball-milled to form a mixed slurry, dried, and granulated to obtain spherical particle powder; the blank after unidirectional pressure preforming and pulse cold isostatic pressing is dried, sintered, ground, and coated with electrodes to obtain the final carbon ceramic closing resistor.
[0105] Characterization and Testing:
[0106] The ceramic resistors obtained in the embodiments and comparative examples were subjected to mechanical grinding and electrode coating to obtain the closing resistors, which were then tested, including: the volume density was tested by weighing method according to GB / T 25995-2010; the compressive strength was tested by pressure testing machine according to GB / T 8489-2006. The resistance of the sample was directly measured by LCR bridge, the temperature coefficient was measured and calculated by combining LCR bridge with high temperature oven, and the voltage coefficient was measured by applying voltage to a lightning reactor. The results are shown in Table 2.
[0107] Table 2
[0108]
[0109] It can be seen from Table 1 that:
[0110] By comparison, the carbon ceramic resistor of Comparative Example 1 only uses the vacuum impregnation method and lacks the impregnation and spinning process played by the centrifuge compared with Comparative Example 1, which will cause the carbon material to be unevenly dispersed in the structure, which is one of the reasons why its performance is worse than that of Example 1. The carbon ceramic resistor of Comparative Example 2 uses the conventional resistor preparation method as the preparation process. In terms of structure, all raw materials are mixed to form a whole, which is prone to agglomeration or segregation, which causes its mechanical and electrical properties to be much lower than the carbon ceramic resistor containing a continuous conductive interlayer prepared in Example 1. The electrical properties and stability of the existing carbon ceramic resistor in Comparative Example 2 are much lower than those of the carbon ceramic resistor containing a continuous conductive interlayer prepared in Example 1. It can be seen that the present invention uses zeolite minerals to prepare a continuous support layer with multi-scale pores, which can improve the mechanical strength of the ceramic, and adopts a vacuum-assisted centrifugal impregnation method to ensure that the carbon material can be fully impregnated into the continuous support matrix. A multi-step sintering method is adopted, and the volume density of the sintered product is ≥2.20g / cm 3The volume density is higher, and the mechanical properties of ceramic resistors containing continuous conductive interlayers are better, and the compressive strength is ≥130MPa.
[0111] From the above, it can be seen that the carbon ceramic resistor with excellent mechanical properties and continuous conductive interlayer prepared by the present invention, when used as an ultra-high / ultra-high voltage closing resistor for electrical use, improves the safety factor of the product and prolongs its service life, thereby ensuring the stability of its resistivity.
[0112] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0113] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0114] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0115] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A carbon ceramic resistor containing a continuous conductive interlayer, characterized in that: include: A continuous ceramic support having a multi-level pore structure; A continuous ceramic filling layer filled in the multi-level pore structure; The continuous carbon conductive layer is filled in the multi-level pore structure and is located between the continuous ceramic support and the continuous ceramic filling layer to form an interlayer.
2. The carbon ceramic resistor containing a continuous conductive interlayer according to claim 1, characterized in that: The continuous ceramic support comprises nanopores, micropores and interface pores with successively increasing pore sizes, forming the multi-level pore structure; Preferably, the pore size of the nanopore is The pore size of the micropore is 100-120 μm; the pore size of the interface pore is 500-800 μm; Preferably, the continuous ceramic support and the continuous ceramic filling layer include mullite; Preferably, the porosity of the continuous ceramic support is 55% to 65%; Preferably, the continuous carbon conductive layer comprises a conductive carbon material, and the conductive carbon material comprises spherical graphite; Preferably, the thickness of the continuous carbon conductive layer is 20 to 50 μm; Preferably, the volume density of the carbon ceramic resistor containing the continuous conductive interlayer is ≥2.20 g / cm 3 , apparent porosity ≤25%, compressive strength ≥130MPa.
3. A method for preparing a carbon ceramic resistor containing a continuous conductive interlayer according to claim 1 or 2, characterized in that: include: Providing a continuous ceramic support body raw material, performing foaming and granulation to obtain a hollow spherical powder, performing compression molding to obtain a first green body, and performing a first sintering to obtain a continuous ceramic support body with a multi-level pore structure; Providing a continuous carbon conductive layer raw material, subjecting the obtained continuous ceramic support to a first impregnation in the continuous carbon conductive layer raw material to obtain a second green body, and then subjecting the green body to a second sintering to form a continuous carbon conductive layer to obtain an intermediate; A continuous ceramic filling layer raw material is provided, and the obtained intermediate is subjected to a second impregnation in the continuous ceramic filling layer raw material to obtain a third green body, which is then subjected to a third sintering to form a continuous ceramic filling layer, thereby obtaining the carbon ceramic resistor containing a continuous conductive interlayer.
4. The method for preparing a carbon ceramic resistor containing a continuous conductive interlayer according to claim 3, characterized in that: Based on the total mass of the continuous ceramic support raw material and the continuous ceramic filling layer raw material being 100 parts, the continuous ceramic support raw material includes 35 to 45 parts of zeolite and 5 to 15 parts of glass powder; Preferably, the preparation method further comprises providing a continuous ceramic support raw material, mixing it with a first additive to obtain a first mixed raw material, and then performing the foaming and granulation on the first mixed raw material; With respect to 100 parts by weight of the total mass of the continuous ceramic support material and the continuous ceramic filling layer material, the first additive includes 0.5 to 2 parts of a first dispersant and 0.5 to 2 parts of a foaming agent; Preferably, the zeolite comprises clinoptilolite, and the zeolite has a pore size of Nanopores; Preferably, the first dispersant comprises at least one of polyacrylamide, sodium humate or polymethylsiloxane; Preferably, the foaming agent includes at least one of propyl gallate, polyether-modified silicone or polyurethane foam; Preferably, except for the foaming agent, the other raw materials of the continuous ceramic support are pre-milled by a first wet ball mill, and then the foaming agent is added to perform the foaming granulation to obtain hollow slurry droplets, and then dried to obtain the hollow spherical powder; Preferably, the ball-to-material mass ratio of the first wet ball milling is (1-3):1, the rotation speed is 400-500 rpm, and the time is 1.5-3 hours; Preferably, the drying temperature is 180-220°C and the drying time is 1-3 hours; Preferably, the press-forming method comprises cold isostatic pressing; Preferably, the pressure of the compression molding is 10 to 20 MPa; Preferably, the first sintering is carried out at a temperature of 1400-1600° C. and for a time of 3-6 hours.
5. The method for preparing a carbon ceramic resistor containing a continuous conductive interlayer according to claim 3 or 4, characterized in that: The continuous carbon conductive layer raw material comprises 0.5 to 4.5 parts of conductive carbon material, based on 100 parts by total mass of the continuous ceramic support raw material and the continuous ceramic filling layer raw material; Preferably, the preparation method further comprises providing a continuous carbon conductive layer raw material, mixing it with a second additive to obtain a second mixed raw material, and then performing the first impregnation on the obtained continuous ceramic support in the second mixed raw material; Relative to 100 parts by weight of the total mass of the continuous ceramic support material and the continuous ceramic filling layer material, the second additive includes 0.5 to 1.5 parts of a second dispersant, 1 to 1.5 parts of polyvinyl alcohol, 0.10 to 0.20 parts of a first surfactant, and 0.5 to 1 parts of a first defoaming agent; Preferably, the conductive carbon material comprises at least one of spherical graphite, expanded graphite or carbon hollow spheres; Preferably, the second dispersant comprises polyvinylpyrrolidone; Preferably, the first surfactant comprises a silane coupling agent; Preferably, the first defoaming agent comprises polydimethylsiloxane; Preferably, the first impregnation method comprises vacuum-assisted centrifugal impregnation; Preferably, the second sintering is performed in a reducing atmosphere, and the temperature of the second sintering is 900-1200°C.
6. The method for preparing a carbon ceramic resistor containing a continuous conductive interlayer according to any one of claims 3 to 5, characterized in that: Based on the total mass parts of the continuous ceramic support raw material and the continuous ceramic filling layer raw material being 100 parts, the continuous ceramic filling layer raw material includes 23 to 27 parts of bauxite, 14 to 16 parts of kaolin, and 9 to 11 parts of calcium feldspar; Preferably, the preparation method comprises providing a continuous ceramic filling layer raw material, mixing it with a third additive to obtain a third mixed raw material, and then subjecting the obtained intermediate to the second impregnation in the third mixed raw material; Relative to 100 parts by total weight of the continuous ceramic support raw material and the continuous ceramic filling layer raw material, the third additive comprises 0.5 to 1.5 parts of a third dispersant, 1 to 1.5 parts of polyvinyl alcohol, 0.10 to 0.20 parts of a second surfactant, and 0.5 to 1 parts of a second defoaming agent; Preferably, the third dispersant comprises polyvinyl pyrrolidone; Preferably, the second surfactant comprises a silane coupling agent; Preferably, the second defoaming agent comprises polydimethylsiloxane; Preferably, the raw material of the continuous ceramic filling layer is pre-milled by a second wet ball mill; Preferably, the ball-to-material mass ratio of the second wet ball milling is (1-3):1, the rotation speed is 300-360 rpm, and the time is 1.5-3 h; Preferably, the second impregnation method comprises vacuum-assisted centrifugal impregnation; Preferably, the temperature of the third sintering is 1200-1400°C.
7. The method for preparing a carbon ceramic resistor containing a continuous conductive interlayer according to claim 5 or 6, characterized in that: The vacuum-assisted centrifugal dipping method is carried out in a manipulator single-cylinder dipping and spinning coating machine, with a vacuum degree of 0.01 to 0.5 atm, a rotation speed of 200 to 400 rpm, and a time of 2 to 5 hours.
8. The method for preparing a carbon ceramic resistor containing a continuous conductive interlayer according to any one of claims 3 to 7, characterized in that: include: (1) Preparation of a continuous ceramic support: A continuous ceramic support material is provided by weight, including 35-45 parts of clinoptilolite, 5-15 parts of glass powder and 0.5-2 parts of a first dispersant, and after mixing, a first wet ball milling is performed, and the ball-material mass ratio is controlled to be (1-3):1, the rotation speed is 400-500 rpm, and the time is 1.5-3 hours to prepare a first mixed slurry; the first dispersant includes at least one of polyacrylamide, sodium humate or polymethylsiloxane; the clinoptilolite has a pore size of Nanopores; adding 0.5 to 2 parts of a foaming agent to the first mixed slurry, wherein the foaming agent includes at least one of propyl gallate, polyether-modified silicone or polyurethane foam; performing foaming and granulation to obtain hollow slurry droplets, and then drying at 180 to 220° C. for 1 to 3 hours to obtain hollow spherical powder; performing cold isostatic pressing of the obtained hollow spherical powder in a mold at 10 to 20 MPa to obtain a first green body, and then performing a first sintering at 1400 to 1600° C. for 3 to 6 hours to obtain a continuous ceramic support having a multi-level pore structure; (2) Preparation of continuous carbon conductive layer: Providing a continuous carbon conductive layer raw material by mass, including 0.5-4.5 parts of a conductive carbon material, 0.5-1.5 parts of a second dispersant polyvinyl pyrrolidone, 1-1.5 parts of polyvinyl alcohol, 0.10-0.20 parts of a first surfactant silane coupling agent, and 0.5-1 parts of a first defoaming agent polydimethylsiloxane, wherein the conductive carbon material includes at least one of spherical graphite, expanded graphite, or carbon hollow spheres, and mixing them to form a second mixed slurry, and using a vacuum-assisted centrifugal impregnation method, the obtained continuous ceramic support body is first impregnated in the second mixed slurry in a manipulator single-cylinder dip-spin integrated coating machine, and the vacuum degree is controlled to be 0.01-0.5atm, the rotation speed is 200-400rpm, and the time is 2-5h to obtain a second green body, and then a second sintering is performed at 900-1200°C in a reducing atmosphere to form a continuous carbon conductive layer to obtain an intermediate; (3) Preparation of continuous ceramic filling layer: Provide a continuous ceramic filling layer raw material by weight, including 23-27 parts of bauxite, 14-16 parts of kaolin, 9-11 parts of calcium feldspar, 0.5-1.5 parts of a third dispersant polyvinyl pyrrolidone, 1-1.5 parts of polyvinyl alcohol, 0.10-0.20 parts of a second surfactant silane coupling agent and 0.5-1 parts of a second defoaming agent polydimethylsiloxane, and perform a second wet ball milling after mixing, control the ball-material mass ratio to (1-3):1, and the rotation speed to 200-400 rpm, for 1.5 to 3 hours, to prepare a third mixed slurry; using a vacuum-assisted centrifugal impregnation method, the intermediate is secondly impregnated in the third mixed slurry in a manipulator single-cylinder dip-spinning coating machine, the vacuum degree is controlled to be 0.01 to 0.5 atm, the rotation speed is 200 to 400 rpm, and the time is 2 to 5 hours to obtain a third green body, and then a third sintering is performed at 1200 to 1400 ° C to form a continuous ceramic filling layer, thereby obtaining the carbon ceramic resistor containing a continuous conductive interlayer; In step (1) and step (3), the total weight of the clinoptilolite, the glass powder, the bauxite, the kaolin and the anorthite is controlled to be 100 parts.
9. A closing resistor, characterized in that: A carbon ceramic resistor containing a continuous conductive interlayer as claimed in claim 1 or 2.
10. A method for manufacturing a closing resistor according to claim 9, characterized in that: The carbon ceramic resistor containing the continuous conductive interlayer is subjected to mechanical grinding treatment and electrode coating in sequence to obtain a closing resistor.
Citation Information
Cited By
Carbon ceramic composite conductive microsphere, ceramic resistor and preparation method
CN120496949A